Buried and Massive Ground Ice on the West Coast of Baidaratskaya Bay in the Kara Sea - N. G. Belova (Лëд и снег)
Using data on the structure, conditions of occurrence (bedding), and the isotope composition of massive ice beds on the West coast of Baydaratskaya Bay it was established that the massive ice beds even occurring in the same outcrop may be related to different genetic types. There are two groups of the massive ice: 1) the «upper» thick (> 3 m) massive ice beds composed by buried basal glacier ice; and 2) the «lower» small ice beds (< 3 m), formed both intrasedimentally and as a result of burial of initially surface ice bodies. Sand thickness which included both groups of the massive ice started its formation before the glacial ice burial. As a result of advancing and later degradation of the glacier, probably moving from the Pay-Khoy ridge or from the Polar Ural, its lower (basal) parts were preserved within the permafrost thickness.